Cultural Presupposition in Translation Strategy from English into Bahasa Indonesia on HBO Television Serial Game of Thrones Season 1 - Adhitya Riska Yunita; Aris Munandar (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2020)
This study aims to identify the cultural presupposition and how the translator applies translation strategies to convey cultural words into the target language. This study used qualitative descriptive for analyzing cultural presuppositions and translation strategies. The data used are utterances that contain cultural presuppositions found in the Game of Thrones television series season 1. This study shows that four types of sub-systems of cultural presupposition were found such as techno-economic, social, and linguistic system. The ideational system in the form of religion, ideology, values, ideas dominate the most compared to other sub-systems. Existential presupposition is the most frequent presupposition which appear followed with factive presupposition. Meanwhile, the translation strategy that frequently used is literal translation followed by borrowing and transposition translation strategy. This study emphasizes that some cultural words such as those belonging to the linguistic sub-system, in their translation to target language require an understanding of the cultural concept of the source language adapted to the cultural concept of target language.